A new alternative for finishing the surface of dental preparations with ultrasonic instruments and CVD technology - Silva, Marina Bacelar; Muramatsu, Layra Catarina Rocha; Silva, Leonardo Alvares Sobral; Marques, Thays Oliveira; Silva, João Maurício Ferraz da; Uemura, Eduardo Shigueyuki (Brazilian Dental Science, 2026)
Objective: This study aimed to evaluate surface roughness and surface finishing quality of bovine dentin prepared using different instrumentation protocols. Conventional high-speed diamond burs were compared with ultrasonic CVD diamond tips to assess their effectiveness in optimizing prosthodontic tooth preparations while preserving dental structure. Material and Methods: Forty bovine teeth were randomly assigned to four experimental groups (n = 10) according to the dentin finishing protocol. The Control group (DT) used a conventional diamond bur at High-speed. Group DT+CR4 employed a conventional bur followed by a CVD diamond tip (CR4) coupled to an ultrasonic device. Group DT+CR4U used a conventional bur followed by two ultrasonic CVD diamond tips (CR4 and ultrafine CR4U). Group DT+FF+RT consisted of a conventional bur followed by a multilaminated carbide bur, an ultrafine diamond tip, and rubber polishing tips. After preparation, surface roughness (Ra) was measured using a contact profilometer, and surface topography was qualitatively analyzed using scanning electron microscopy (SEM). Data were submitted to descriptive and variance analyses with a 95% confidence interval. Results: The Control group showed significantly higher surface roughness values (Ra = 3.46 ± 0.89; p < 0.001) compared with all experimental groups. No statistically significant differences were observed among the experimental protocols (Ra = 1.94 ± 0.80; 1.87 ± 0.43; 1.83 ± 0.66; p > 0.05). SEM analysis revealed that the DT+CR4 and DT+CR4U groups exhibited more regular and homogeneous dentin surfaces than the Control group, while DT+FF+RT presented the smoothest surface pattern. Conclusion: Tooth preparations performed with ultrasonic CVD diamond tips resulted in more regular and homogeneous dentin surfaces and significantly reduced surface roughness compared with conventional diamond burs alone. These findings support the use of CVD diamond tips as a viable and conservative alternative for the finishing of prosthodontic tooth preparation. KEYWORDS Dental cavity preparation; Prosthodontic tooth preparation; Scanning electron microscopy; Surface properties; Ultrasonic.